Analisis Kadar Flavonoid dan Fenolat pada Kulit Buah Manggis (Garcininia mangostanaL.) - Rezki, Atika Putri; Gonggo, Siang Tandi; Sabang, Sri Mulyani (Universitas Tadulako, 2017)
This study aimed to determine flavonoid and phenolic levels from the mangosteen bark samples. The preparation process of the sample was performed by extraction through maceration technique using HCl 1% in ethanol and for the phenolic using ethanol. Levels of both analit were determined using a UV-Vis spectrophotometer at the wavelength of 510 nm and 700 nm for the flavonoid, and 765 nm for the phenol. The results showed that flavonoids and phenol levels in the mangosteen bark samples were 1.271 mg/g and 12.373 mg/g.